Educational Media Management from a Qur'anic Perspective - Siti Nurmahyati (Indonesian Academy of Social and Religious Research (IASRR), 2023)
Educational media needs to be managed so that it runs effectively and efficiently. Management of educational media can be done based on the Qur'an. This research is of a qualitative type. Qualitative methods allow the author to identify and explain the management of educational media from a comprehensive Qur'anic Perspective. In writing, the author uses the study of literature. The literature used is in the form of journals and books to explore information and data regarding the object and subject of research. The result of research Educational or learning media is an object that can be sensed, especially vision and hearing, both inside and outside the classroom, which is used as a connecting tool (communication media) in the process of teaching and learning interactions to improve the effectiveness of student learning outcomes. Various verses in the Qur’an talk about educational media. There is a form of educational media management recommended as ordered by the Quran, namely audio-visual educational media.